Predicted luteal phase length has no influence on success of vitrified-warmed blastocyst transfer in natural cycle - M. Reljič; J. Knez (BMC, 2018)
Abstract Background This study evaluated the influence of menstrual cycle length, menstrual cycle variability and predicted luteal phase length on the success of vitrified-warmed blastocyst transfer in natural menstrual cycle using progesterone for luteal phase supplementation. Methods Consecutive women undergoing vitrified-warmed blastocyst transfer in natural menstrual cycle between January 2013 and December 2015 were included in this retrospective study. Patients' characteristics, clinical data and data about menstrual cycle length in the last year were collected from our database. Predicted luteal phase length (LPL) was defined as the period starting at ovulation (one day after positive urinary LH test) and ending on the last day before predicted menses, based on women's usual, minimal and maximal menstrual cycle length data. Logistic regression was used to identify the predictors significantly associated with live-birth. Results A total of 1195 FETs (frozen-thawed embryo transfers) resulted in 457 (38.24%) clinical pregnancies, 82 (17.94%), miscarriages and 371 live births (31.04%). There were no statistically significant differences in menstrual cycle length, menstrual cycle variability, day of LH surge, day of FET and predicted LPL between FET cycles resulting in live birth and those not resulting in live birth. In the multivariate logistic regression model, only women's age (OR 0.93, 95% CI: 0.90-0.96), transfer of morphologically optimal blastocysts (OR 2.17, 95% CI: 1.59-2.94) and endometrium thickness (OR 1.10, 95% CI: 1.03-1.17) were important independent prognostic factors for live birth. Conclusion Menstrual cycle length, menstrual cycle variability and predicted LPL do not seem to be an important factor influencing live birth after FET in natural cycles with progesterone supplementation. Results of our study suggest that FET should not be cancelled if LH surge is detected before or after the predicted period in natural cycle with progesterone supplementation.